Smart Sensor Based Obstacle Detection for High-Speed Unmanned Surface Vehicle. Issue 16 (2015) - Hermann, D.; Galeazzi, R.; Andersen, J.C.; Blanke, M.
Abstract: This paper describes an obstacle detection system for a high-speed and agile unmanned surface vehicle (USV), running at speeds up to 30m/s. The aim is a real-time and high performance obstacle detection system using both radar and vision technologies to detect obstacles within a range of 175 m. A computer vision horizon detector enables a highly accurate attitude estimation despite large and sudden vehicle accelerations. This further facilitates the reduction of sea clutter by utilising a attitude based statistical measure. Full scale sea trials show a significant increase in obstacle tracking performance using sensor fusion of radar and computer vision.